Indicações para a construção de um modelo organizacional para inserção competitiva dos pequenos produtores de castanha de caju do Ceará no mercado globalizado - Costa, Larisse Oliveira (2008)
The development model adopted by Brazil as a result of industrial growth during the decade of 30 of last century, gives priority to the economical growth based on urban industry. Spreading out to the Northeast region via SUDENE and to the state of the Ceará, as a result this model brought intensified concentration of income, rural exodus, increase of social inequalities and of poverty, besides the exclusion of the formal market and of most of the economically active population (PEA) of the country. It seems obvious that it does not serve society as a whole and needs to be modified. The best form of doing it is by promoting local endogenous development. One of the forms of putting into operation this local endogenous development is by organizing the economic activity of small rural producers through cooperatives as a way of making them active economic agents. This research analyzes one of the principal local chains of production – the chain of the cashew nut (ACC), in which the small rural producers answer for most of the production of the basic raw material. Nevertheless, they did not receive compatible benefits with in relation to its importance, putting them on the border of economic and social inclusion, since the middlemen and the processors derive most of the profit produced by the chain. In order for this chain to contribute in a publicly-known way to improve the quality of life of these producers it is necessary have a balance between their internal links and integration with their external environment, besides adequate organization and management in order to become competitive in the world-wide market. In this context, a well-organized and operational model is introduced, aiming to contribute to competitive insertion of small producers of cashew nuts of the state of the Ceará into the world market. As a base we have the concepts of poverty, inequality, agriculture, agrobusiness, agroindustrial systems, productive chains, supply chains, supply chain management, integration, cooperation and cooperatives. The model proposes to structure three principal internal segments of the chain in order to act in a systematic form, integrated, organized and coordinated, thus stimulating, the development of the chain, and contributing n such a manner that the small producers of cashew nuts in Ceará also begin to process it, and to receive benefits proportional to the risks and intrinsic uncertainties associated with their businesses